Nepogodbena odškodninska odgovornost strokovnjakov nasproti tretjim osebam - Dular, Drago (Podjetje in delo, 2023)
It is customary for professionals working in liberal professions to be liable to their clients for breaches of contracts under which they have been commissioned to provide expert opinions. This does not preclude their liability for damages on a non-contractual basis when they have breached professional law in the preparation of their opinions. In the area of liability of experts to third parties, the above distinctions of liability, with their different purposes, are less to third parties, which is due to the fact that, although the non-contractual liability of experts to third parties is limited to the relationship between experts and third parties, it is at the same time embedded in the matrix of tripartite relations and can be understood on the basis of an analysis of those relationships. This also has an impact on the specific damages to third parties, which is expressed as pure economic damages and is conceptually linked to the characteristic of the third party. Third parties are persons to whom expert opinions are not addressed but who may, under certain conditions, rely on them. In such a context, the presumption of illegality of the experts' conduct becomes crucial to understanding third-party harm. Third parties are characterised by the fact that they can only arise in the context of triangular relationships and third-party damage can also be understood in the context of those relationships. Given that the Slovenian courts, when dealing with third-party damage, have so far referred to the concept of legally relevant damages, which is also derived from European tort law, in relation to damage caused by the provision of false information, the author of this article argues that this concept of damage refers to damage suffered by the contracting entity and not by third parties. The notion of pure economic damage that can be suffered by a third party in the context of tripartite relationships was developed by German, English and, to an extent, Austrian courts, and is now widely established in comparative law. In Slovenian law, in order to establish the damage in question, it would also be necessary to refer to the corresponding legal basis, determined according to the praeter legem criterion.
Keywords: ekonomska škoda; naročniki; nepogodbena odškodninska odgovornost; obligacijska razmerja; odškodninska odgovornost; pravna relevantna škoda; strokovnjaki; tretje osebe